Reseña de: Bravo Caro, Juan Jesús, Roldán Paz, Lorena e Ybáñez Worboys, Pilar (Coords.), El Mediterráneo: sociedades y conflictos - Pinto Tortosa, Antonio Jesús (Espacio Tiempo y Forma. Serie IV, Historia Moderna, 2025)
Reseña de: Bravo Caro, Juan Jesús, Roldán Paz, Lorena e Ybáñez Worboys, Pilar (Coords.), El Mediterráneo: sociedades y conflictos, Madrid, Sílex, 2020, 587 págs. ISBN 978-84-18388-33-0.